A Fail-Safe Decision Architecture for CCAM Applications - Rodríguez-Arozamena, Mario; Matute, Jose; Pérez, Joshué; Ozbay, Burcu; Tezcan, Deryanur; Begecarslan, Enes; Mutlukaya, Irem; Buquerin, Kevin Gomez; Volkersdorfer, Tina; Hof, Hans Joachim (Springer, 2026)
In the context of Connected, Cooperative, and Automated Mobility (CCAM), precise ego-vehicle positioning and environmental status assessment are crucial. However, these tasks can be susceptible to sensor failures, misuse, and cyberattacks. Automation disengagements and system redundancy are common strategies to achieve Minimum Risk Conditions when failures occur. This paper presents a Fail-Safe decision architecture formulated within the framework of the SELFY project (https://selfy-project.eu/). The main aim is to reduce inaccuracies in GNSS-derived positioning through the incorporation of sensor fusion, AI-guided situational assessment, trajectory planning, and mode decision components. Additionally, the architecture has been designed to enable real-time updates and communication with external entities, including the Vehicle Security Operations Centre.
CRIS-Team Scopus Importer:2025-10-31
Keywords: CCAM; Decision; Fail-Safe; Fallback Strategy; Situational Awareness; Urban Scenarios